1998
DOI: 10.1164/ajrccm.157.6.9704086
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Immunoreactive Interleukin-6 in Cystic Fibrosis

Abstract: We measured circulating and sputum-sol concentrations of interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-alpha), neutrophil elastase-alpha1-antiproteinase complex (NEAPC), and C-reactive protein (CRP) in an exacerbation, after antibiotic treatment, and in clinically stable patients with cystic fibrosis and chronic pulmonary infection with Pseudomonas aeruginosa. The aim was to determine the compartmental patterns of a proinflammatory and anti-inflammatory cytokine compared with other markers of inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(97 citation statements)
references
References 29 publications
8
88
1
Order By: Relevance
“…However, in that group, no significant correlations were found between cytokine levels and bone density. Our present findings differ from those reported previously showing elevated cytokines in patients with CF [29][30][31][32][33][34]. One explanation is the use of inhaled glucocorticoids by all study participants in the current sample.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, in that group, no significant correlations were found between cytokine levels and bone density. Our present findings differ from those reported previously showing elevated cytokines in patients with CF [29][30][31][32][33][34]. One explanation is the use of inhaled glucocorticoids by all study participants in the current sample.…”
Section: Discussioncontrasting
confidence: 99%
“…The proresorptive cytokines, tumor necrosis factor α (TNF-α), interleukin 1β (IL-1β), and interleukin 6 (IL-6) [28], stimulate bone resorption and/or osteoclast formation. Two reports have shown that TNF-α production by lung macrophages was elevated in patients with CF [29,30], and other studies have shown elevations of serum TNF-α [31], IL-1β [30], and IL-6 [30,32,33] concentrations in these patients. Haworth et al [34] found an inverse correlation between skeletal losses and serum IL-6 concentrations over a 1-year period in a study of young adults with CF.…”
Section: Introductionmentioning
confidence: 86%
“…An association between serum IL-8 levels and bacterial numbers or inflammation was not observed. While studies in older CF patients with chronic lung disease report modest elevations of circulating inflammatory mediators [26,27], these may only represent increased local production of cytokines and may not be of any pathophysiological significance.…”
Section: Discussionmentioning
confidence: 98%
“…We did not assess airway inflammation and cannot determine whether changes in systemic measures of inflammation reflect inflammatory changes in the lungs. Three studies have reported modest correlations between blood-based biomarker levels and select markers of airway inflammation (IL-8, TNF-a, TGF-b 1 ) during CF pulmonary exacerbations (31)(32)(33). This suggests that assay of systemic inflammatory markers may, to some extent, reflect inflammatory burden in the lungs.…”
Section: O2 Saturationmentioning
confidence: 99%